Association between Recipient IL-15 Genetic Variant and the Prognosis of HBV-Related Hepatocellular Carcinoma after Liver Transplantation. (15th October 2017) - Zhang, Tao; Liu, Yuan; Peng, Xu; Fan, Junwei; Peng, Zhihai
Abstract : Objective . To investigate the association of donor and recipient IL-15 genetic variants with HCC recurrence and prognosis after LT. Methods . A total of 112 liver transplant patients with HBV-related HCC were enrolled. IL-15 rs10519613 and rs13122930 were genotyped in donors and recipients. Results . Recipient IL-15 rs10519613 polymorphism was found to be significantly related to HCC recurrence after LT. In multivariate analysis, tumor thrombus, UCSF criteria, and recipient IL-15 rs10519613 genotypes were independent predictive factors of HCC recurrence after LT. Kaplan-Meier survival analysis demonstrated that patients with recipient IL-15 rs10519613 CA/AA genotypes had a decreased disease-free survival and overall survival than those with the CC genotype. Recipient IL-15 rs10519613 genetic variant could improve survival prediction when combined with the UCSF criteria. Furthermore, Cox proportional hazard regression analysis revealed that tumor size (p = 0.012, p = 0.623 ), tumor thrombus (p = 0.011, p = 0.015 ), UCSF criteria (p = 0.471, p = 0.013 ), and recipient IL-15 rs10519613 genotype (p = 0.039, p = 0.008 ) were independent factors of predicting DFS and OS. Conclusions . Recipient IL-15 rs10519613 polymorphism was associated with HCC recurrence after LT and might be a potential genetic marker for the clinical outcome of HCC patients treated with LT.